2009
DOI: 10.1088/0960-1317/20/1/015007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of residual stress and its effects on the vibrational characteristics of piezoelectric-based multilayered microdiaphragms

Abstract: In this study, residual stress influences on the vibrational behavior of piezoelectric circular microdiaphragm-based biosensors are investigated theoretically and experimentally. The piezoelectric microdiaphragm was first fabricated by combining sol-gel PZT thin film and MEMS technology. The stress measurements by the wafer curvature method and the micro-Raman technique demonstrate that high tensile stresses are generated in the upper films (Pt/PZT/Pt), while the silicon oxide layer experiences a compressive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…The diaphragm mechanical model is used to calculate the volume displacement in (20). The equivalent circuit representation of the two-port model is shown in Fig.…”
Section: Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diaphragm mechanical model is used to calculate the volume displacement in (20). The equivalent circuit representation of the two-port model is shown in Fig.…”
Section: Transductionmentioning
confidence: 99%
“…The authors reported two diaphragm designs with diameters of 1.2 and 1.42 mm and a thickness of 15 μm. The responses [20].…”
mentioning
confidence: 99%
“…This is a specialized application of the Quartz crystal microbalance as a biosensor. 225 Recently, microdiaphragm piezoelectric-based biosensors have been successfully applied as a biological diagnostic tool in air and liquid media. 226 Thermometric-and magnetic-based sol-gel biosensors are seldom being reported and very few publications could be found in Web of Science.…”
Section: Biosensors Based On Other Transducing Principlesmentioning
confidence: 99%
“…The diaphragm was fabricated by bonding a piezoelectric plate onto a SOI (silicon on insulator) wafer with 20μm thick device layer [12]. The thickness of the piezoelectric layer was thinned down to about 40μm by using chemical/mechanical polish.…”
Section: Deflection/deformation Measurementmentioning
confidence: 99%